Rainfall-discharge relationships for monsoonal climates - Steenhuis, Tammo S.; Taylor, J.; Easton, Z.M.; Collick, A.; Giesen, Nick van de; Liebe, Jens R.; Ahmed, A.A.; Andreini, Marc (2009)
Methods for estimating runoff that have been developed for temperate climates may not be suitable for use in the monsoonal climates of Africa, where there is a distinct dry season during which soils dry out to a considerable depth. This has a distinct effect on runoff generation that is not captured by ?the temperate climate? models. The scope of this tool is to develop a simple water balance method for predicting river discharge. Water balance models have been shown to better predict river discharge in regions with monsoonal climates than alternative methods based on the United States Department of Agriculture-Soil Conservation Service (USDA-SCS) curve number. The latter is an empirical-based model developed in the USA that does not apply to monsoonal climates with distinct dry and wet periods.